1983
DOI: 10.1002/jcp.1041140304
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidyl choline and the growth in serum‐free medium of vascular endothelial and smooth muscle cells, and corneal endothelial cells

Abstract: Liposomes made by sonication of egg yolk phosphatidyl choline support the proliferation of low-density bovine vascular and corneal endothelial cells, and vascular smooth muscle cells maintained on basement laminacoated dishes and exposed to a defined medium supplemented with transferrin. The optimal growth-promoting effect of phosphatidyl choline was observed at concentrations of 25 micrograms/ml for low-density cultures of vascular smooth muscle cells, and 100 micrograms/ml for vascular and corneal endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 42 publications
1
10
1
Order By: Relevance
“…This can be ascribed to the formation of vesicles due to the exceeding Choline II which takes after the structure of phosphoglyceride composing cell membranes. 34,35 Possibility of subsistence of vesicles even after freeze-drying was presumed by the traces of blank particles as shown in Figure 1(c). These is ascribed to the formation of vesicles that has not enough alginate polymers to form the solid nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…This can be ascribed to the formation of vesicles due to the exceeding Choline II which takes after the structure of phosphoglyceride composing cell membranes. 34,35 Possibility of subsistence of vesicles even after freeze-drying was presumed by the traces of blank particles as shown in Figure 1(c). These is ascribed to the formation of vesicles that has not enough alginate polymers to form the solid nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was tentatively assigned to the presence of phosphorylcholine in the degradation fluid. Phosphorylcholine is natural substance, and has been identified as growth‐promoting to vascular and corneal endothelial cells 30. It is also suggested that phosphorylcholine could induce a high‐level expression of vascular endothelial growth factor (VEGF), which is substantial in the proliferation of endothelial cells 31…”
Section: Resultsmentioning
confidence: 99%
“…First attempts to perform SF EC culture were already described over 30 years ago, even though those studies were focused on EC biology rather than on their possible therapeutic potential (Fujii, Cheng, & Gospodarowicz, ; Gorfien, Spector, DeLuca, & Weiss, ; Hoshi & McKeehan, ). Some of the supplements tested included EGF, bFGF, BPE, human hepatoma cell‐conditioned medium, and matrix protein coatings, among others.…”
Section: Current Alternatives To the Use Of Fbs In Ec Culturementioning
confidence: 99%